Micropropagação do porta-enxerto Mr. S. 2/5 (Prunus cerasifera x Prunus spinosa) - Gallo, Cibele Merched (2012)
Although fruiting plants can be propagated by several methods, commercial seedlings of Prunus are obtained by grafting a scion on a rootstock. In Rio Grande do Sul State, because of the proximity of the canning industry, the rootstocks originate from the disposal pits of late maturing cultivars, allowing the occurrence of varietal mixtures, and consequently, the formation of orchards with uneven plants. On the other hand, vegetative propagation leads to the formation of uniform plants, because they keep the characteristics of the mother-plant. This propagation may be made by several methods, for example, micropropagation. Thus, to develop protocols for vegetative propagation will contribute to the production of seedlings of Prunus spp. in southern Brazil. The aim of this work was to optimize in vitro multiplication and rooting, and the acclimatization of shoots from the rooting medium with rootstock Mr. S. 2/5.This work was divided into two chapters, one on the in vitro multiplication, and the second refers to in vitro rooting and acclimatization. In the first chapter, composition of salts, culture medium pH, source and concentration of carbohydrate, and concentration of IBA were tested. In the second chapter, the objective was to evaluate the effect of IBA concentration, and the permanence time of the shoots in the culture medium, in vitro rooting, and their survival during acclimatization phase. At the multiplication stage, the explants cultivated in MS medium, pH 5.2, showed a higher number of shoots. However, the source and concentration of carbohydrate had no influence on number and length of the shoots formed. In relation to IBA concentrations, supplemented mediums with 0.06mgL-1 increased formation of shoots, but had no significant influence on their length. With respect to in vitro rooting phase and acclimatization, shoots cultivated in a culture medium with 1.6mgL-1 IBA, during 12 days, showed high percentage of rooting, approximately 90%, as well as higher percentage of surviving plants in the acclimatization phase.